Implementasi Hukum Islam Pada Perilaku Ekonomi Komunitas Pedagang Banjar - Adim, Abd.; Sukarni, Sukarni; Hanafiah, M.; Muhajir, Ahmad (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research discusses several aspects of the economic behavior of the Banjar traders community, economic activities, types of trading businesses, and the implementation of Islamic law on economic behavior, as well as how Islamic law can be applied to economic practices if linked to the Banjar treasures which include traditions (Business, Work, and time), the value of money and business competition that is developing in the Kalimantan region, especially among the Banjar people. Reviewing from historical facts and phenomena that appear in reality and writings in circulation, the economic behavior of the Banjar trading community has its own uniqueness, known as religious traders, although the problems that arise often trigger big questions, is it true that the economic behavior of the Banjar traders community has implemented Islamic law in ìthe trading area to support the religious trader's statement. According to Max Weber, religion is a differentiator between Western and Eastern culture, meanwhile, according to Jaquin Austria, the Islamic economic school is a stronger economic school and now this school of thought has led the world, so that the influence of religious thought on the economy provides an insight into social stratification. In this research, we try to dissect and present the actual facts by prioritizing the fundamental values in the economic behavior of the Banjar traders community from the perspective of Islamic law as the main basis for muamalah. Keywords: Implementation, Islamic Law, Economic Behavior, Banjar Traders Abstrak Penelitian ini membahas beberapa hal perilaku ekonomi komunitas pedagang Banjar, aktivitas ekonomi, jenis-jenis usaha perdagangan, dan implementasi hukum Islam pada perilaku ekonomi, serta bagaimana hukum Islam tersebut bisa diterapkan pada praktik ekonomi jika dipertautkan dengan khazanah Banjar yang meliputi tradisi (Usaha, Kerja dan waktu), Nilai uang dan Persaingan usaha yang berkembang di wilayah kalimantan, terutama di kalangan orang Banjar. Ditinjau dari fakta sejarah maupun fenomena yang nampak pada realita dan tulisan yang beredar, bahwa perilaku ekonomi komunitas pedagang Banjar memiliki keunikan tersendiri yang dikenal dengan pedagang religius, meskipun problem yang muncul sering kali memicu pertanyaan besar, benarkah perilaku ekonomi komunitas pedagang Banjar sudah mengimplementasikan hukum Islam di area perdagangan untuk mendukung statement pedagang yang agamis tadi. Menurut Max Weber agama merupakan pembeda antara budaya Barat dan Timur, sedangkan, menurut Jaquin Austria mengatakan bahwa mazhab ekonomi Islam adalah mazhab ekonomi yang lebih kuat dan sekarang mazhab ini telah memimpin dunia, sehingga pengaruh pemikiran keagamaan terhadap perekonomian memberikan pandangan tentang stratifikasi sosial. Pada penelitian ini mencoba membedah dan menyajikan fakta sebenarnya dengan mengedepankan nilai-nilai yang mendasar pada perilaku ekonomi komunitas pedagang Banjar ditinjau dari perspektif hukum Islam sebagai landasan pokok bermuamalah. Kata kunci: Implementasi, Hukum Islam, Perilaku Ekonomi, Pedagang Banjar